Asking questions in biology : - Barnard, Chris (Pearson Education, 2001)
The aim of the course is to introduce studentsin the biological sciences to the skill of observation and enquiry, but focusing on the process of enquiry, how to formalate hypotheses and predicttions from raw information,...